The effect of moral foundations and personality dimensions of health workers on patient satisfaction with healthcare services - Terzić, Neda; Pečujlija, Mladen; Cvetković, Sreten; Lukić Šarkanović, Mirka (Vojnosanitetski pregled, 2020)
Background/Aim. Working with people in medical practice requires knowledge of the basic principles of personality psychology. The aim of this research was to examine the influence of moral foundations and personality dimensions of health workers on patient satisfaction with health service, as well as determining the factors influencing their satisfaction. Methods. The research was conducted using the Big Five Inventory (BFI), theMoral Foundations Questionnaire (MFQ) and the Questionnaire of patient satisfaction with healthcare service, from October 2014 to March 2016. The survey involved 693 respondents: 329 healthcare workers (44 males and 285 females) and 364 patients (154 males and 210 females). Results. With the increase of the openness of healthcare professionals, the patients' satisfaction was also growing. Regarding moral foundations of healthcare workers, there was an opposite trend ‒ with lower authoritativeness of healthcare workers, patient satisfaction was greater. Finally, with more pronounced purity of healthcare workers there was a decrease in the level of patientsʼ satisfaction with the received healthcare service. Conclusion. There is a direct association between the moral foundations and personality dimensions of health workers, and patientsʼ satisfaction with healthcare service. Thus, any strategy for improving the quality of healthcare service should take into account personal characteristics of healthcare workers. Healthcare professionals are expected to fulfill their life and professional tasks in as a human way as possible, since preservation of the health and helping to overcome an illness, in case it develops, are the basic values of every human being. It should result in more clearly defined priorities for improvement of the quality of work of healthcare workers.
Keywords: health services; health personnel; morals; patient satisfaction; surveys and questionnaires